An unusual case of relative polycythemia with complication of pseudocyst of pancreas - Venkat, Shruthi Kamal; Sattar, Reshma; Kumar, Dinesh (International Surgery Journal, 2017)
Relative polycythemia is a term used to describe an elevation of the hematocrit level either caused by an acute transient state of hemoconcentration associated with intravascular fluid depletion or a chronic sustained relative polycythemia caused by contraction of the plasma volume. Relative polycythemia can occur when the plasma volume is reduced due to intravascular volume depletion during acute pancreatitis episode, complicating as pseudocyst of pancreas. We report a case of Relative Polycythemia with pseudocyst of Pancreas a secondary complication of pancreatitis.